Problems of Female Students in Mastering Intajiah Skills - Sofia Shoha; Abdul Kirom (Universitas Al-Amien Prenduan, 2025)
Arabic language learning can be defined as a process of conditioning students to understand four skills: writing skills, speaking skills, listening skills, and reading skills. These skills are categorized into receptive skills, such as reading and listening, and productive skills, such as writing and speaking. This research aims to identify the linguistic problems in learning Arabic skills for 4th-semester intensive students both in the classroom and in the dormitory, identify the non-linguistic problems in learning Arabic skills for 4th-semester intensive students both in the classroom and in the dormitory. The researcher uses a descriptive qualitative research approach with a field research type, employing the Miles and Huberman model. Data is collected through various data collection techniques, including interviews, observation, and documentation. The results of this study indicate that it has been implemented with intensive fourth-semester female students at university of Al-Amien Prenduan in campus and in the dormitory. The productive skill issues stem from various linguistic forms, which include, problems in composing verbal structures, problems in composing nominal structures, problems in vocabulary composition, and problems with language code-switching. Non-linguistic factors contributing to these issues include, lack of motivation to learn, insufficient knowledge before entering the Islamic boarding school, and uneven mastery of productive skill among female students. It can be understood that with a strong desire to learn Arabic, non-pesantren female students can master productive skill on par with boarding scool graduates.